A Clinical Evaluation Of Therapeutic Drug Monitoring Of Phenytoin In Epileptic Patients In A Tertiary Care Teaching Hospital, Chennai, Tamilnadu: A Randomized, Open Label Comparative Study - V. SIVASANKARI M.D,; C.B. THARANI M.D,; S.GOBINATHAN M.D., DM, (International Journal of Pharma and Bio Sciences, 2012)
Phenytoin is effective for treatment of generalized tonic-clonic seizures and partial seizures. Therapeutic drug monitoring of phenytoin is useful as it has narrow therapeutic index, saturable kinetics and inter-individual variations. A randomized, open lable, comparative study was done in 60 epileptic patients to assess the clinical impact of therapeutic drug monitoring of phenytoin. Patients of age 18 to 50 years on phenytoin monotherapy with subtherapeutic concentration (<10µg /ml) were included and allocated into two groups. In group I, dosage was adjusted by using therapeutic drug monitoring, whereas in group II, dosage was adjusted on clinical grounds. Serum levels of phenytoin were determined by High Performance Liquid Chromatography. The results were analyzed. There was a significant increase in mean serum phenytoin concentration with reduction in the seizure frequency in group I (p=0.001).To conclude, therapeutic drug monitoring assisted dosage modification provides better seizure control with fewer adverse effects than group II patients.